1995
DOI: 10.1177/074823379501100601
|View full text |Cite
|
Sign up to set email alerts
|

Atsdr Evaluation of Health Effects of Chemicals

Abstract: This document provides public health officials, physicians, toxicologists, and other interested individuals and groups with an overall perspective of the toxicology of mirex and chlordecone. It contains descriptions and evaluations of toxicological studies and epidemiological investigations and provides conclusions, where possible, on the relevance of toxicity and toxicokinetic data to public health. Additional substances will be profiled in a series of manuscripts to follow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 430 publications
(1,113 reference statements)
1
6
0
Order By: Relevance
“…The bioaccumulation observed in M. rosenbergii is consistent with the fact that CLD has a high potential of bioaccumulation in aquatic organisms, based on its physicochemical properties (ATSDR et al, 1995). This result is in agreement with previous studies highlighting the CLD concentration in different organisms.…”
Section: Chlordecone Bioaccumulationsupporting
confidence: 82%
See 1 more Smart Citation
“…The bioaccumulation observed in M. rosenbergii is consistent with the fact that CLD has a high potential of bioaccumulation in aquatic organisms, based on its physicochemical properties (ATSDR et al, 1995). This result is in agreement with previous studies highlighting the CLD concentration in different organisms.…”
Section: Chlordecone Bioaccumulationsupporting
confidence: 82%
“…This observation could be explained by the distribution of CLD in tissues of prawns. Indeed, because of its structure and binding properties, CLD binds preferentially to serum proteins such as lipoproteins or albumin and therefore, its distribution in the whole organism is quite different compared to other organochlorines (ATSDR et al, 1995;Newhouse et al, 2009). For example, the accumulation of CLD is highest in the liver (Newhouse et al, 2009) while other organochlorine pesticides such as HCB or p,p -DDE are preferentially distributed in the adipose tissue (Gomez-Catalan et al, 1991;Soine et al, 1982).…”
Section: Chlordecone Bioaccumulationmentioning
confidence: 99%
“…Experimental studies with birds and mammals show effects similar to those reported in occupationally exposed humans including neurological effects, oligospermia, and hepatomegaly (reviewed in Faroon et al 1995 ). Gestational and perinatal chlordecone exposures in rodents have been shown to be detrimental to normal fetal development and to impair neurobehavior during preweaning and postweaning development (Mactutus et al 1982 , 1984 ; Mactutus and Tilson 1984 , 1985 ).…”
Section: What We Knew About Chlordecone Toxicity In 1999?mentioning
confidence: 61%
“…Long-term feeding with chlordecone also produced an increased incidence of liver tumors mediated by tumor promotion rather than initiation (Reuber 1979 ; Sirica et al 1989 ). Proteinuria, never observed in highly exposed men despite appropriate investigations (Guzelian 1982 ), was shown to be the most sensitive toxic endpoint in rats (Faroon et al 1995 ) and is currently used as the basis for establishing acceptable levels of human exposure.…”
Section: What We Knew About Chlordecone Toxicity In 1999?mentioning
confidence: 99%
See 1 more Smart Citation